THE INFLUENCE OF CORPORATE IMAGE, USER IMAGE, AND PRODUCT IMAGE TOWARD PURCHASE DECISION ON MUI HALAL FOOD CERTIFICATION: A Study on Pizza Hut Restaurant in Malang - Novianti, Ratih Diyah; naryo, Su (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research aims to examine the influence of Corporate Image, User Image, and Product Image toward Purchase Decision on MUI Halal Food Certification, a study on Pizza Hut Restaurant in Malang. The type of this research is Explanatory Research. The research is conducted in all Pizza Hut Restaurant outlets in Malang (Pizza Hut Semeru, Pizza Hut Matos, Pizza Hut Ciliwung, and Pizza Hut Suhat). 150 questionnaires were distributed randomly to Pizza Hut Muslim consumers who have visited the outlets for more than one in a year in all Pizza Hut restaurants in Malang. The sampling technique used purposive sampling and the research instruments were tested using the Validity Test, Reliability Test, and Classical Assumption Test. The hypothesis testing used F-Test and T-Test. The multiple regression analysis result shows that Corporate Image, User Image, and Product Image have significant effect simultaneously and partially toward Purchase Decision.The dominant test shows that User Image is the most dominant variable influencing the Purchase Decision. Overall, the independent variables: Corporate Image, User Image, and Product Image have contribution as 70.6% toward dependent variable: Purchase Decision while the rest 29.4% are described by other variables beyond this research.The result of this research can be applied for Marketing Strategy. The company should retain the brand image with halal image in order to always have a positive image in the consumers’ eyes that will influence their decision in purchasing decision. Keywords: Corporate Image, User Image, Product Image, Brand Image, MUI Halal Certification, Purchase Decision